2020
DOI: 10.1016/j.jcv.2020.104660
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-COV N2 Gene: Very low amounts of viral RNA or false positive?

Abstract: Background The detection of a low amount of viral RNA is crucial to identify a SARS-CoV-2 positive individual harboring a low level of virus, especially during the convalescent period. However, the detection of one gene at high Cycle threshold (Ct) has to be interpreted with caution. In this study we address this specific issue and report our real-life experience. Study design A total of 1639 nasopharyngeal swabs (NPS) were analyzed with Xpert® Xpress SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…Decreasing viral load might also occur in true negative cases, i.e., non-infected people, of whom the first sample was a false-positive, possibly due to contamination or high test sensitivity. This can be more often the case in people with no history of clinical signs relevant to COVID-19, as shown in the current study, findings that are in line with those of Falasca et al [18].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Decreasing viral load might also occur in true negative cases, i.e., non-infected people, of whom the first sample was a false-positive, possibly due to contamination or high test sensitivity. This can be more often the case in people with no history of clinical signs relevant to COVID-19, as shown in the current study, findings that are in line with those of Falasca et al [18].…”
Section: Discussionsupporting
confidence: 93%
“…In the same study, a second NPS collected 24 h after the first, indicated that 12 of 17 samples were negative (70.5%). Laboratory data correlated well with clinical data further supported these laboratory findings, as only 2 among these 17 persons developed clinical signs relevant to COVID-19 [18]. Katz et al [19] reported false-positive rRT-PCR reactions in a setting for urgent head and neck surgery and otolaryngologic emergencies, leading to delay of urgent surgical procedures and transfer of people to COVID-19-designated units [19].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…35 , 36 False-positive real-time RT-PCR results in clinical material with low viral loads have been observed for PCR assays. 37 By comparing three RT-RPA assays and validating them with clinical samples, we were able to pick a highly accurate RPA assay, i.e., RdRP RT-RPA.…”
Section: Discussionmentioning
confidence: 99%
“…False negative results may be due to sample inhibitors, poor amplification efficiency, and reduced precision in low concentration samples. False positives could arise from contaminants or poor test specificity [41]. In any case, the sensitivity and specificity of the RT-PCR methods used to detect SARS-CoV-2 in seminal fluid have not been evaluated [42].…”
Section: Discussionmentioning
confidence: 99%